Teoría de la imagen ensayos sobre representación verbal y visual - Mitchell, W. J. Thomas 1942-; Hernández Velázquez, Yaiza; Mitchell, W. J. Thomas (Tres Cantos, España : Akal, 2009)
Fruto de las investigaciones de uno de los más importantes teóricos de la representación visual en América, "Teoría de la imagen" ofrece una detallada explicación del juego entre lo visible y lo legible en la cultura, desde la literatura a las artes visuales y los medios de comunicación. Partiendo de películas contemporáneas y controvertidas, como "Haz lo que debas de Spike Lee" y "JFK" de Oliver Stone, así como de la cobertura que los medios de comunicación hacen de las noticias nacionales, W. J. T. Mitchell examina e ilustra la fuerza modeladora que poseen las imágenes para despertar o acallar el debate público, la emoción colectiva y la violencia política. Teoría de la imagen obtuvo en 1996 el premio Charles Rufus Morey de la College Art Association y, en 1997, el premio Gordon E. Laing concedido por la University of Chicago Press.
Teoria de la imagen -- Imágenes textuales -- Textos pictoriales -- Imágenes y poder -- La imágen y la esfera pública.
Resumen tomado de la página web de la editorial
on a dark desert highway, cool wind in my hair warm smell of colitas, rising up throught the air up ahead in the distance, i saw a shimmering light my head grew heavy and my sight grew dim i had to stop for the night there she stood in the doorway; i heard the mission bell and i was thinking to myself, ”this could be heaven or this could be hell” then she lit up a candle and she showed me the way there were voices down the corridor, i thought i heard them say... welcome to the hotel California such a lovely place, such a lovely place such a lovely face plenty of room at the hotel California any time of year, you can find it here her mind is Tiffany.twisted, she got the Mercedes Benz she got a lot of pretty, pretty boys, that she call friends how they dance in the courtyard, sweet summer sweat. Some dance to remember, some dance to forget So i called up the captain, ”please bring me my wine” he said ”we haven´t had that spirit here since 1969” and still those voices are calling from the far away, wake up in the middle of the night just to hear them say... welcome to the hotel California such a lovely place, such a lovely place such a lovely face they livin´it up the hotel California what a nice surprise, bring your alibis mirrors on the ceiling, the pink champagne on ice and she said’we are all just prisioners here, of our own device’ and in the master’s chambers they gathered for the feast they stabbed her with their steely knives but they just can’t kill the beast
General
Keywords: Comunicación visual -- Filosofía; Medios de comunicación social -- Filosofía; Arte -- Filosofía; Imágenes-Interpretación; Imágenes y poder